Combined MEK Inhibition and BMP2 Treatment Promotes Osteoblast Differentiation and Bone Healing in Nf1Osx−/− Mice. (January 2015) - de la Croix Ndong, Jean; Stevens, David M; Vignaux, Guillaume; Uppuganti, Sasidhar; Perrien, Daniel S; Yang, Xiangli; Nyman, Jeffry S; Harth, Eva; Elefteriou, Florent
ABSTRACT Neurofibromatosis type I (NF1) is an autosomal dominant disease with an incidence of 1/3000, caused by mutations in the NF1 gene, which encodes the RAS/GTPase‐activating protein neurofibromin. Non‐bone union after fracture (pseudarthrosis) in children with NF1 remains a challenging orthopedic condition to treat. Recent progress in understanding the biology of neurofibromin suggested that NF1 pseudarthrosis stems primarily from defects in the bone mesenchymal lineage and hypersensitivity of hematopoietic cells to TGFβ. However, clinically relevant pharmacological approaches to augment bone union in these patients remain limited. In this study, we report the generation of a novel conditional mutant mouse line used to model NF1 pseudoarthrosis, in which Nf1 can be ablated in an inducible fashion in osteoprogenitors of postnatal mice, thus circumventing the dwarfism associated with previous mouse models where Nf1 is ablated in embryonic mesenchymal cell lineages. An ex vivo–based cell culture approach based on the use of Nf1flox/flox bone marrow stromal cells showed that loss of Nf1 impairs osteoprogenitor cell differentiation in a cell‐autonomous manner, independent of developmental growth plate–derived or paracrine/hormonal influences. In addition, in vitro gene expression and differentiation assays indicated that chronic ERK activation in Nf1‐deficient osteoprogenitors blunts the pro‐osteogenic property of BMP2, based on the observation that only combination treatment with BMP2 and MEK inhibition promoted the differentiation of Nf1‐deficient osteoprogenitors. The in vivo preclinical relevance of these findings was confirmed by the improved bone healing and callus strength observed in Nf1osx−/− mice receiving Trametinib (a MEK inhibitor) and BMP2 released locally at the fracture site via a novel nanoparticle and polyglycidol‐based delivery method. Collectively, these results provide novel evidence for a cell‐autonomous role of neurofibromin in osteoprogenitor cells and insights about a novel targeted approach for the treatment of NF1 pseudoarthrosis. © 2014 American Society for Bone and Mineral Research.